PEMBERIAN PUPUK KANDANG SEBAGAI PEMBENAH TANAH UNTUK PERTUMBUHAN DAN HASIL MELON (Cucumis melo L.) DI ULTISOL - Eka Nurjanah; Sumardi Sumardi; Prasetyo Prasetyo (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2020)
[MANURE APPLICATION AS A SOIL AMENDMENT TO PROMOTE GROWTH AND YIELD OF MELON (Cucumis melo L.) IN ULTISOL]. The application of manure may overcome soil fertility problems in Ultisol triggered by low pH, high P retention, high content of Al and Fe, and low CEC. The objective of this study was to determine the optimum dose of different manures applied to promote the best growth and yield of melon. The study was conducted from February to May 2019 at the Experimental Plot of the Faculty of Agriculture, University of Bengkulu. Three different manures (chicken, cow, and goat manure) were applied at 5, 10, 15, and 20 tons/ha. These treatments were arranged in Completely Randomized Design with three replications. The results show that the enhancement in chlorophyll content (SPAD index) was highest in plots solely applied with 20 tons ha-1 manure, whereas application of manure even at 20 tons/ha had no effects on melon yield and its components. Manure types solely promoted plant height, maturity date, fruit diameter, and soluble solid content (Brix). Melon growth and yield were not affected by combined application of manure type and dose. These indicate that application of manure types irrespective of the amount applied failed to solve fertility problems in Ultisol where melon was grown.